The dual nature of metacommunity variability. Issue 12 (22nd September 2021) - Lamy, Thomas; Wisnoski, Nathan I.; Andrade, Riley; Castorani, Max C. N.; Compagnoni, Aldo; Lany, Nina; Marazzi, Luca; Record, Sydne; Swan, Christopher M.; Tonkin, Jonathan D.; Voelker, Nicole; Wang, Shaopeng; et al.
Abstract : There is increasing interest in measuring ecological stability to understand how communities and ecosystems respond to broad‐scale global changes. One of the most common approaches is to quantify the variation through time in community or ecosystem aggregate attributes (e.g. total biomass), referred to as aggregate variability. It is now widely recognized that aggregate variability represents only one aspect of communities and ecosystems, and compositional variability, the changes in the relative frequency of species in an assemblage, is equally important. Recent contributions have also begun to explore ecological stability at regional spatial scales, where interconnected local communities form metacommunities, a key concept in managing complex landscapes. However, the conceptual frameworks and measures of ecological stability in space have only focused on aggregate variability, leaving a conceptual gap. Here, we address this gap with a novel framework for quantifying the aggregate and compositional variability of communities and ecosystems through space and time. We demonstrate that the compositional variability of a metacommunity depends on the degree of spatial synchrony in compositional trajectories among local communities. We then provide a conceptual framework in which compositional variability of 1) the metacommunity through time and 2) among local communities combine into four archetype scenarios: spatial stasis (low/low), spatial synchrony (high/low), spatial asynchrony (high/high) and spatial compensation (low/high). We illustrate this framework based on numerical examples and a case study of a macroalgal metacommunity in which low spatial synchrony reduced variability in aggregate biomass at the metacommunity scale, while masking high spatial synchrony in compositional trajectories among local communities. Finally, we discuss the role of dispersal, environmental heterogeneity, species interactions and suggest future avenues. We believe this framework will be helpful for considering both aspects of variability simultaneously, which is important to better understand ecological stability in natural and complex landscapes in response to environmental changes.